2006
DOI: 10.1002/aqc.732
|View full text |Cite
|
Sign up to set email alerts
|

Recent human‐induced salinity changes in Ramsar‐listed Orielton Lagoon, south‐east Tasmania, Australia: a new approach for coastal lagoon conservation and management

Abstract: ABSTRACT1. Many coastal lagoons in eastern Australia have changed as a result of recent human activities. However, it is often difficult to determine the extent of change and the ecological implications. A palaeoecological approach allows a quantitative assessment of how an aquatic ecosystem changes and responds to human impacts beyond what is possible with historical data or monitoring programmes.2. Orielton Lagoon (south-east Tasmania, Australia) is a Ramsar-listed coastal wetland of international importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 36 publications
2
24
1
Order By: Relevance
“…The most common and widespread taxa (Table 4) are considered cosmopolitan species, characteristic of brackish, coastal and marine water bodies (Witkowski et al 2000) and have been identified in previous Australian coastal diatom studies (e.g. Fluin et al 2007;Haynes et al 2007;Saunders et al 2007;Taffs et al 2008). Table 3 for site codes and water chemistry information This study demonstrated that diatom assemblages in southeast Australian coastal lakes, lagoons and estuaries are primarily influenced by salinity.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…The most common and widespread taxa (Table 4) are considered cosmopolitan species, characteristic of brackish, coastal and marine water bodies (Witkowski et al 2000) and have been identified in previous Australian coastal diatom studies (e.g. Fluin et al 2007;Haynes et al 2007;Saunders et al 2007;Taffs et al 2008). Table 3 for site codes and water chemistry information This study demonstrated that diatom assemblages in southeast Australian coastal lakes, lagoons and estuaries are primarily influenced by salinity.…”
Section: Discussionmentioning
confidence: 59%
“…Salinity has previously been found to be the overriding environmental variable influencing Australian diatom communities and diatom-salinity (or -conductivity) relationships have been described (e.g. Hodgson et al 1997;Blinn and Bailey 2001;Gell et al 2002;Philibert et al 2006;Saunders et al 2007;Tibby et al 2007;Taukulis and John 2009). With the exception of Hodgson et al (1997) and Saunders et al (2007), none of these studies were conducted in coastal ecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations